Usp18 Mediates D-Dopachrome Tautomerase-Induced Astrocytic Inflammation After Spinal Cord Injury - Zhang X; Hou Y; Cai R; Zhou Y; He B; Cao Z; Li A; Song H; Wang Y; Jiang H; Qi L; Wang Y (Journal of Inflammation Research)
Xingyuan Zhang,1,* Yuxuan Hou,1,* Rixin Cai,1 Yue Zhou,1 Bingqiang He,1 Zhilong Cao,1,2 Aicheng Li,1 Honghua Song,1 Yingjie Wang,1 Haiyan Jiang,3 Lei Qi,4 Yongjun Wang1,5 1Key Laboratory of Neuroregeneration of Jiangsu and Ministry of Education, Co-innovation Center of Neuroregeneration, Nantong University, Nantong, 226001, People’s Republic of China; 2Department of Intensive Care Unit, Nantong Third People’s Hospital, Nantong, 226001, People’s Republic of China; 3Health Management Center, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China; 4Department of Emergency Medicine, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China; 5Department of Burn and Plastic Surgery, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Qi, Department of Emergency Medicine, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China, Email qilei723@ntu.edu.cn Yongjun Wang, Key Laboratory of Neuroregeneration, Nantong University, 19 Qixiu Road, Nantong, 226001, People’s Republic of China, Tel + 86-513-85051818, Fax +86-513-85511585, Email wyjbs@ntu.edu.cnBackground: D-dopachrome tautomerase (D-DT), a homolog of macrophage migration inhibitory factor (MIF), has been revealed to promote astrocytic inflammation and worsen neuropathology following spinal cord injury (SCI). So far, the mechanism about D-DT-activated astrocytic inflammation remains elusive. Ubiquitin-specific peptidase 18 (Usp18) is an active player in regulating innate immunity through ISG15-deconjugated dependent or independent manner in multiple cell types. Whether D-DT activates astrocytic inflammation via regulation of Usp18 deserves further study.Methods: SCI model was prepared by cord contusion at T8-T10 of rats. The expression changes of D-DT and Usp18 were examined by ELISA, Western blot, RT-PCR or immunohistochemistry. Primary astrocytes were treated by different concentration of D-DT, either for transcriptome sequencing or for analysis of D-DT-mediated expression of Usp18. Knockdown of CD74 or Usp18 expression was performed by siRNA transfection of astrocytes. The locomotor functions were assessed using the Basso, Beattie, and Bresnahan (BBB) locomotor scale.Results: Usp18 was significantly upregulated in the astrocytes at lesion sites following SCI, in parallel with the elevation of D-DT protein levels. D-DT inhibitor 4-CPPC remarkably decreased the astrocytic expression of USP18. Transcriptome sequencing of D-DT-stimulated primary astrocytes identified that Usp18 was the hub modulator of D-DT-mediated astrocytic inflammation. D-DT-mediated expression of Usp18 was able to activate MAPKs, contributing to the production of proinflammatory cytokines and chemokines. Specifically, phosphorylation of P38 kinase was shown to promote the expression of Usp18 by formation of a positive feedback loop. Administration of D-DT inhibitor 4-CPPC at lesion sites following SCI significantly reduced the protein levels of Usp18 and ameliorated functional deficits of rat hindlimb locomotion.Conclusion: SCI-induced elevation of D-DT at lesion sites activates astrocytic inflammation via upregulating the expression of Usp18. Identification of this novel regulator associated with astrocytic inflammation will provide an alternative target for clinical therapy of neuroinflammation.Keywords: D-DT, Usp18, astrocyte, inflammation, ubiquitination, spinal cord